Kegiatan Pengabdian Masyarakat dalam Rangka Edukasi Masyarakat Terhadap Hipertensi serta Deteksi Dini Penyakit Gagal Ginjal Sebagai Komplikasi dari Hipertensi - Donatila Mano S; Pasuarja Jeranding Ezra; Agnes Marcella; Yohanes Firmansyah (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
Hypertension and kidney failure are two types of diseases related to kidney health. Hypertension or high blood pressure can cause damage to the kidneys, while kidney failure is a condition in which the kidneys cannot function properly to build up metabolic waste and fluids from the body. Hypertension can cause damage to the small blood vessels in the kidneys, so that the kidneys cannot excrete waste properly. As a result, harmful substances can accumulate in the body and cause organ damage. If hypertension cannot be controlled properly, it can cause kidney damage and eventually lead to kidney failure. Failure is a kidney condition in which the kidneys cannot function properly to remove metabolic wastes and fluids from the body. Kidney failure can occur for a variety of reasons, including untreated hypertension, diabetes, congenital kidney disease, and use of certain medications. If left untreated, kidney failure can lead to accumulation of waste in the body and serious complications such as anemia, osteoporosis, heart disease and even death. Treatment of hypertension and kidney failure usually involves medication and lifestyle changes. Treatment includes the use of drugs prescribed by a doctor and the management of complications that may occur. Lifestyle changes include managing a healthy diet, reducing salt and fat consumption, exercising regularly, avoiding smoking, and managing stress. Early detection is very important in the management of hypertension and kidney failure. Regular blood pressure checks, urine tests to detect protein in the urine, and blood tests to detect levels of creatinine, blood glucose, and cholesterol in the blood can help detect risks and early symptoms of kidney disease.